HIV and dementia: prevalence and risk factors - Lara Gurgel Fernandes Távora; Thais Martins Figueiredo; Ramille Moitas Krammer de Mesquita; Fernando Ricarte Bezerra; Bruno Pinheiro Aquino; Jeová Keny de Baima Colares (Universidade de Fortaleza, 2016)
Objective: To determine the prevalence of patients at risk of developing HIV-associated neurocognitive disorder (HAND) and identify factors possibly associated with its occurence. Methods: Quantitative cross-sectional study conducted at the Specialized Care Service (Serviço de Atendimento Especializado - SAE) for HIV/Aids of the Integrated Medical Care Center (Núcleo de Atendimento Médico Integrado - NAMI) of the University of Fortaleza (Universidade de Fortaleza - UNIFOR), Fortaleza, Ceará, Brazil. We reviewed medical records of all 249 patients that started medical follow-up at SAE/NAMI since its foundation (August/2010) until January/2014, including in the analysis those who completed the international HIV dementia scale - IHDS during routine medical visits. Epidemiological, clinical and laboratory variables were collected in addition to IHDS score and the sample was classified in two groups: patients with IHDS≥10 (Group 1) and IHDS<10 (Group 2). Chisquared test was used for categorical variables and student t test, mann whitney test and linear regression were used for numerical variables. Results: The study population consisted of 178 patients with mean IHDS score of 9.5 (+/- 1.6). HAND prevalence was 41.6% (74/178) (IHDS<10). These patients presented older mean age (37.4 years) and longer mean time from HIV diagnosis to medical follow-up than the others (10.1 months) when compared to Group 2 (31 years old and 4.6 months, respectively), suggesting that these two variables were possibly associated with HAND occurrence. Conclusion: The IHDS application showed a high prevalence of HAND in the study population. More advanced age and longer time from HIV diagnosis to medical follow-up are possibly associated with its occurence.